2013
DOI: 10.1177/1074248413486355
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanum Carbonate Delays Progression of Coronary Artery Calcification Compared With Calcium-Based Phosphate Binders in Patients on Hemodialysis

Abstract: This pilot study suggested that LC delayed progression of CAC in patients on HD compared with CC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 34 publications
5
36
0
Order By: Relevance
“…The potential explanation for the mortality decrease associated with the use of non-calcium-based binders might be related to slowing vascular calcification. This is also supported by additional evidence which suggest that switching phosphate binder from calcium carbonate to lanthanum carbonate delayed the progression of calcium calcification in patients on HD 24 .…”
Section: The Control Of Hyperphosphatemia: Oral Phosphate-binding Drugssupporting
confidence: 70%
See 1 more Smart Citation
“…The potential explanation for the mortality decrease associated with the use of non-calcium-based binders might be related to slowing vascular calcification. This is also supported by additional evidence which suggest that switching phosphate binder from calcium carbonate to lanthanum carbonate delayed the progression of calcium calcification in patients on HD 24 .…”
Section: The Control Of Hyperphosphatemia: Oral Phosphate-binding Drugssupporting
confidence: 70%
“…Lanthanum carbonate, which is a non-aluminum-and non-calcium-containing phosphorus binder, has confirmed long-term safety 24,25 . Its main excretion route is through the bile, and it is thought to be advantageous for patients with renal insufficiency.…”
Section: Safety and Tolerability Considerationsmentioning
confidence: 99%
“…In recent years, the association between PTH and CAC has become a research hotspot. The results of previous studies suggested that PTH levels were not associated with the baseline CAC score (CACS), but with CAC progression (7)(8)(9)(10)(11). All of the patients included in these studies suffered from kidney failure with or without hemodialysis.…”
Section: Introductionmentioning
confidence: 92%
“…We performed a prospective randomized interventional study that compared the effect of lanthanum carbonate and calcium carbonate on the progression of CAC (Fig. 6) [98]. Treatment with lanthanum carbonate was more effective compared to calcium carbonate in preventing the progression of CAC in patients on hemodialysis; regression by 6.4% was shown in the lanthanum-treated group vs. 41.2% progression in those receiving calcium carbonate.…”
Section: Phosphate Bindersmentioning
confidence: 99%
“…Several clinical trials expected the beneficial inhibitory effect of sevelamer hydrochloride on the [96,97]. There are several studies that compared the effect of lanthanum carbonate on vascular calcification with calcium-based phosphate binders [98][99][100][101]. We performed a prospective randomized interventional study that compared the effect of lanthanum carbonate and calcium carbonate on the progression of CAC (Fig.…”
Section: Phosphate Bindersmentioning
confidence: 99%